Generation of a doxycycline-inducible ETV2 expression cell line using PiggyBac transposase system - Meng Zhou; Jie Ni; Pufeng Huang; Xujie Liu (Stem Cell Research, 2023)
E26 transformation-specific variant 2 (ETV2), as a member of Ets family of transcription factors, plays an important role in embryonic vasculogenesis, angiogenesis and hematopoiesis. Here, based on H9 cell line and PiggyBac technology, we generated a doxycycline-inducible ETV2 (Dox-ETV2-H9) embryonic stem cell (ESC) line. The Dox-ETV2-H9 cells maintain normal morphology, karyotype as well as high expression of pluripotent markers. In comparison with previous studies that employing costly ETV2 modRNA to improve differentiation from ESCs into endothelial cells (ECs), the tet-on system in Dox-ETV2-H9 cells could precisely manipulate ETV2 expression, which enables ECs differentiation process more efficient and controllable upon addition of doxycycline.